Publicaciones de José Enrique Martínez Fernández - Álvarez Méndez, Natalia; Martínez Cantón, Clara Isabel; Trabado Cabado, José Manuel (Tropelías. Revista de Teoría de la Literatura y Literatura Comparada, 2017)
Publicaciones de José Enrique Martínez Fernández